2016
DOI: 10.1002/cncr.30264
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of minimal residual disease negativity according to the salvage status in patients with relapsed/refractory B‐cell acute lymphoblastic leukemia

Abstract: Background Minimal residual disease (MRD) assessment predicts survival in newly diagnosed acute lymphoblastic leukemia (ALL). Its significance in relapsed/refractory ALL is less clear. Methods We identified 78 patients with relapsed/refractory B-ALL who achieved morphologic response with inotuzumab ozogamicin (n=41), blinatumomab (n=11) or mini-hyper-CVD plus inotuzumab (HCVD+ino; n=26) given in either salvage 1 (S1; n=46) or salvage 2 (S2; n=32) and who had MRD assessment by multiparameter flow cytometry at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…The favorable outcomes of these patients are in line with our previous report, which showed that ASCT for patients with morphologic and flow MRD responses in salvage 1 resulted in the best outcomes, with a cure rate approaching 50%. 9 This is in contrast to the outcomes of patients treated in salvage 2, where the achievement of a flow MRD response and subsequent ASCT had no impact on survival.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The favorable outcomes of these patients are in line with our previous report, which showed that ASCT for patients with morphologic and flow MRD responses in salvage 1 resulted in the best outcomes, with a cure rate approaching 50%. 9 This is in contrast to the outcomes of patients treated in salvage 2, where the achievement of a flow MRD response and subsequent ASCT had no impact on survival.…”
Section: Discussionmentioning
confidence: 91%
“…6 Better results were obtained in patients treated earlier (salvage 1 vs salvage 2 or later) and in patients with a minimal disease burden; such patients can experience long-term survival. [8][9][10][11] The addition of inotuzumab ozogamicin as targeted immunotherapy to effective low-intensity chemotherapy in patients with R-R ALL has shown promising results with an overall response rate of 80% and a median survival of 11 months versus 6 months with single-agent inotuzumab ozogamicin in similar patient populations. 10 Such a strategy may translate into a significant long-term survival benefit when it is used for patients in first salvage.…”
Section: Introductionmentioning
confidence: 99%
“…In another analysis, patients who achieved an MRD response with inotuzumab ozogamicin, blinatumomab, or mini‐hyperfractionated cyclophosphamide, vincristine and doxorubicin plus inotuzumab in first salvage therapy had better outcomes compared with those in second salvage therapy. A numerical improvement in OS after HSCT versus no HSCT was noted among patients treated in first salvage therapy with MRD response, although this difference lacked statistical significance ( P = .28) …”
Section: Discussionmentioning
confidence: 99%
“…A numerical improvement in OS after HSCT versus no HSCT was noted among patients treated in first salvage therapy with MRD response, although this difference lacked statistical significance (P = .28). 22 To our knowledge, the role of HSCT after MRD remission in patients with R/R ALL remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, the positive impact of MRD negativity reported recently for ALL patients in first salvage 15 was not observed here. The partial efficacy of the Cheprall regimen in a population with such a poor prognosis suggests that epratuzumab should be tested in first-line schedules, since it may also contribute to decreasing the level of MRD, especially before allogeneic hematopoietic stem cell transplantation, with the hope of increasing patients' survival.…”
Section: Characteristics Of Patients N=30mentioning
confidence: 52%